Effectiveness of MES Palm Oil Surfactant using Core Flooding and Spontaneous Imbibition in EOR methods - Setiati, Rini; Haryono, Muhammad Furqon; Ristawati, Arinda; Samsol; Akbar, Fahrurrozi; Bharoto; Sumirat, Iwan; Ramadhan, Ranggi Sahmura (Journal of Earth Energy Science, Engineering, and Technology, 2026)
Enhanced Oil Recovery (EOR) is one of the methods developed to optimize oil extraction from wells that still have reserve potential. This study focuses on the application of surfactant injection techniques using vegetable-based surfactants derived from Methil Ester Sulfonate (MES) from palm oil. The objective of this study is to evaluate the effectiveness of MES surfactants in increasing the recovery factor through two main testing methods, namely core flooding test and spontaneous imbibition. The tests were conducted under two variations of conditions, namely salinity of 5,000 ppm at a concentration of 0.5% and salinity of 10,000 ppm at a concentration of 2%. The test results showed that in the core flooding method, a salinity of 5,000 ppm with a concentration of 0.5% produced the highest recovery factor of 84.74%, while a salinity of 10,000 ppm with a concentration of 2% produced 62.63%. Meanwhile, in spontaneous imbibition testing, the recovery factor achieved was 51.94% for a concentration of 0.5% and 45.24% for a concentration of 2%. Based on these results, it can be concluded that the most optimal conditions for increasing oil recovery with palm oil MES surfactant are achieved in the core flooding test method with a salinity of 5,000 ppm and a concentration of 0.5%..